Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films